Socioeconomic inequality in oral health behavior in Iranian children and adolescents by the Oaxaca-Blinder decomposition method: the CASPIAN- IV study. Issue 1 (December 2016) - Safiri, Saeid; Kelishadi, Roya; Heshmat, Ramin; Rahimi, Ali; Djalalinia, Shirin; Ghasemian, Anoosheh; Sheidaei, Ali; Motlagh, Mohammad; Ardalan, Gelayol; Mansourian, Morteza; Asayesh, Hamid; Sepidarkish, Mahdi; et al.
Abstract Background The present study set to describe the socioeconomic inequality associated with oral hygiene behavior among Iranian pediatric population. Methods A representative sample of 13486 school students aged 6–18 years was selected through multistage random cluster sampling method from urban and rural areas of 30 provinces in Iran. Principle Component Analyses (PCA) correlated variables summarized as socioeconomic status (SES). Association of independent variables with tooth brushing was assessed through logistic regression analysis. Decomposition of the gap in tooth brushing between the first and fifth SES quintiles was assessed using the counterfactual decomposition technique. To assess the relation between tooth brushing and each socioeconomic category, Concentration Index (C) and the slope index of inequality (SII) were used, representing the linear regression coefficient. Results The participation rate was 90.6 % (50.7 % boys and 75.6 % urban inhabitants). The mean age of participants was 12.47 ± 3.36 years. The frequency of tooth brushing increased across SES quintiles, prevalence of tooth brushing between the first and fifth quintile, under 20 % difference, increased from 58.22 (95 % CI: 56.24, 60.20) to 78.61 (95 % CI: 77.00, 80.24). Only 3 % of the difference is explained by the factors considered in the study, and 17 % remained unknown. Residence area, family size, and smoking status made a significant contribution to the gap between the first and last SE groups. Residence area [ −2.01 (95 % CI: −3.46, −0.55)] was along the maximum levels of gaps between SE categories. Conclusions The findings revealed a socio-economic inequality in oral health behavior in Iranian children and adolescents. Also, factors influencing oral health are addressed to develop and implement complementary public health actions.